Edukasi Pemanfaatan Kulit Buah Salak Pondoh terhadap Bakteri Eschericia coli dan Bakteri Salmonella typhi - Jon Kenedy Marpaung; Widya Fitri; Julia Susanti; Martin Suhendri; Enjelina Br Sembiring Kembaren (Jurnal Nusantara Berbakti, 2025)
Cottage salak (Salacca zalacca (Gaertn.) Voss) is one of the tropical fruits that not only has high nutritional value, but also contains bioactive compounds that have the potential to be natural antibacterial. The skin of the salak pondoh fruit is often considered waste, even though this part is rich in chemical compounds such as flavonoids, saponins, phenols, tannins, alkaloids, chlorogenic acid, ferrulic acid, and protocatetic acid. These compounds are known to have biological activity that is able to inhibit the growth of pathogenic microorganisms. Escherichia coli and Salmonella typhi bacteria are the main causes of diarrhea and typhoid fever that affect many people, especially in areas with poor sanitation. Infection of these two bacteria can cause intestinal tissue damage, dehydration, and even serious complications if not treated immediately. Therefore, efforts to find alternative antibacterial agents from natural ingredients such as salak pondoh bark are important. This study aims to test the effectiveness of ethanol extract of salak pondoh bark against E. coli and S. typhi bacteria. Extraction was carried out by the maceration method using ethanol as a solvent, then continued with testing of antibacterial activity using the disc diffusion method. The concentration of the extract was tested on several variations to determine the minimum concentration capable of providing an optimal buffer zone against both test bacteria. The community service program integrated with this research aims to increase public understanding regarding the potential of salak pondoh skin as a natural antibacterial. Education is carried out through counseling and demonstrations of making simple extracts that can be used to clean household appliances or prevent microbial contamination of foodstuffs. With this approach, it is hoped that the community can use salak pondoh skin waste more productively, while reducing dependence on synthetic chemicals that have the potential to cause side effects.